Darboux Curves in Lorentzian Three Dimensional Heisenberg Group - Suroglu, Gulden Altay; Korpinar, Talat (Soc Paranaense Matematica, 2021)
In this paper, a new characterization for darboux curves in Heis(3) is completely given. Then, a new classification for translation surface, which is generated by darboux curve in Heis(3) is obtained.
Keywords: Heisenberg group; Lorentz metric